Overview of the Progress in Practice and Experimental Research in Petroleum and Natural Gas Engineering - Xiaobin Li; Jiaxue Li; Pengfei Zhao; Gan Feng; Lei Zhao (Energies)
The global energy system is undergoing unprecedented changes [...]